Difference in the lipid nanoparticle technology employed in three approved siRNA (Patisiran) and mRNA (COVID-19 vaccine) drugs - Suzuki, Yuta; Ishihara, Hiroshi (Drug metabolism and pharmacokinetics, 2021)
Nucleic acid therapeutics are developing into precise medicines that can manipulate specific genes. However, the development of safe and effective delivery system for the target cells has remained a challenge. Lipid nanoparticles (LNPs) have provided a revolutionary delivery system that can ensure multiple clinical translation of RNA-based candidates. In 2018, Patisiran (Onpattro) was first approved as an LNP-based siRNA drug. In 2020, during the coronavirus disease 2019 (COVID-19) outbreak, LNPs have enabled the development of two SARS-CoV-2 mRNA vaccines, Tozinameran (Comirnaty or Pfizer-BioNTech COVID-19 vaccine) and Elasomeran (Spikevax or COVID-19 vaccine Moderna) for conditional approval. Here, we reviewed the state-of-the-art LNP technology employed in three approved drugs (one siRNA-based and two mRNA-based drugs) and discussed the differences in their mode of action, formulation design, and biodistribution.